The financial sector, macroeconomic policy and performance - Robert A. Feldman; Nancy Wagner (EIB Papers, 2002)
A healthy and developing financial sector is a key support to balanced and sustainable economic growth. And as the countries of central Europe - the Czech Republic, Hungary, Poland, Slovakia, and Slovenia - approach EU membership and ultimately adoption of the euro, the litmus test for financial sector performance will be its success in supporting such growth and the process of convergence to EU income levels.
Keywords: 330; Finanzsektor; Finanzmarkt; Wirtschaftswachstum; EU-Erweiterung; Osteuropa